Therapeutic Potential of Luteolin on Cancer - Melisa Çetinkaya; Yusuf Baran (Vaccines, 2023)
Cancer is a global concern, as the rate of incidence is increasing each year. The challenges related to the current chemotherapy drugs, such as the concerns related to toxicity, turn to cancer therapeutic research to discover alternative therapy strategies that are less toxic to normal cells. Among those studies, the use of flavonoids—natural compounds produced by plants as secondary metabolites for cancer therapy—has been a hot topic in cancer treatment. Luteolin, a flavonoid that has been present in many fruits, vegetables, and herbs, has been identified to exhibit numerous biological activities, including anti-inflammatory, antidiabetic, and anticancer properties. The anticancer property of Luteolin has been extensively researched in many cancer types and has been related to its ability to inhibit tumor growth by targeting cellular processes such as apoptosis, angiogenesis, migration, and cell cycle progression. It achieves this by interacting with various signaling pathways and proteins. In the current review, the molecular targets of Luteolin as it exerts its anticancer properties, the combination therapy that includes Luteolin with other flavonoids or chemotherapeutic drugs, and the nanodelivery strategies for Luteolin are described for several cancer types.